2010
DOI: 10.1111/j.1865-1682.2010.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for African Swine Fever in Nigeria, 2006-2009

Abstract: African swine fever (ASF) has had significant economic and social impact in Nigeria since 1997. However, there has been no effective national response to bring it under control. In this report, we confirm that ASF is still prevalent and widespread in Nigeria. Results from both serosurveillance and virological analyses indicated that ASF is present in most of the agro-ecological zones of the country. Nine per cent (9%) of serum samples and 48% of tissue samples were positive for ASF virus antibody and genome, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 8 publications
1
58
0
Order By: Relevance
“…It may become necessary to revise the existing programmes or expand them to reach and accommodate more small-scale/emerging farmers. The majority of farmers got their pigs from neighbouring farms (68%) whose disease status was unknown, or from markets (27%), which are usually collection areas and have been identified as sources of disease redistribution and dissemination (Costard et al, 2009;Fasina et al, 2010). It should be noted that many of the farmers interviewed confirmed having kept back ASF survivor pigs, or selling them, and taking sick pigs to live animal markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may become necessary to revise the existing programmes or expand them to reach and accommodate more small-scale/emerging farmers. The majority of farmers got their pigs from neighbouring farms (68%) whose disease status was unknown, or from markets (27%), which are usually collection areas and have been identified as sources of disease redistribution and dissemination (Costard et al, 2009;Fasina et al, 2010). It should be noted that many of the farmers interviewed confirmed having kept back ASF survivor pigs, or selling them, and taking sick pigs to live animal markets.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in West Africa demonstrated that areas with a high level of pigrelated activities, which includes the marketing, consumption and farming of pigs, tend to have a higher prevalence of ASF, and that a significant reduction in ASF prevalence would only be possible if on-farm biosecurity protocols are fostered, and the affected pig farmers are compensated, inclusive routine surveillance and a testing system are instituted, and market and transportation systems are reorganized (Fasina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The farmers tend to present sick and unthrifty pigs for slaughter at abattoirs first, without determining the cause of sickness, some of which may be ASF (Randriamparany et al, 2005;Fasina et al, 2010). Since the ASF virus is present in the tissues and body fluids of slaughtered sick pigs, massive environmental contamination and possible farm infection may result.…”
Section: Discussionmentioning
confidence: 99%
“…Maps were drawn based on the reports of El-Hicheri (1998), Luther, et al (2007b, Owolodun et al (2007), Fasina et al (2010), Owolodun et al (2010) well as pest and rodent control measures (OR = 4.94; CI 95% = 1.84, 13.29; P = 0.002),…”
Section: Outbreaks Were Confirmed By Means Of Combinations Of Clinicomentioning
confidence: 99%
See 1 more Smart Citation